Pengaruh Loan to Deposit Ratio Terhadap Nilai Perusahaan yang Dimoderasi Capital Adequacy Ratio pada Bank Umum Nasional Konvensional - Sochib, Sochib; Liyundiro, Fetri Setyo; Yulianti, Ani (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2024)
This research aims to identify the role of CAR in influencing the Loan to Deposit Ratio (LDR) on company value as measured by the Tobins Q value. The object of this research is conventional national commercial banks in Indonesia which are listed on the Indonesia Stock Exchange (BEI) during the 2017-2021 period. . From the sampling method used, 24 banks were selected as samples which were analyzed using the Moderated Regression Analysis (MRA) technique. The research results show that the Loan to Deposit Ratio (LDR) has a significant influence on company value and the Capital Adequacy Ratio (CAR) cannot moderate the influence of LDR on company value. This research states that the Capital Adequacy Ratio (CAR) cannot strengthen the influence of LDR on company value as measured by Tobins Q. CAR or bank capital adequacy functions to strengthen the bank's resilience to risks that may arise from loans with poor collectability quality.